Pengembangan Dashboard Layanan Tiket dengan Fitur Penyajian Visual pada Travel Agent - Angel Lieta (Universitas Kristen Maranatha, 2025)
The development of information technology has encouraged many companies, including in the tourism sector, to utilize digital systems to make operations more efficient. One of the problems faced by Travel Agents is the delivery of ticket information to customers which is still done manually via WhatsApp. This process is prone to typing errors and is less uniform in presenting information. The purpose of this final project is to develop a dashboard that is able to display ticket information visually, structured, and professionally. The data used is master data without the involvement of a database or backend. The theory used refers to the principle of developing information systems with a bottom-up approach, which consists of system requirements analysis, DFD, PSPEC, data dictionary, ERD, and interface design. The system development method used is prototyping. The result of this system development is a dashboard application that displays ticket information in real-time under the input form, equipped with automatic generate features and screenshots for sending via social media. The conclusion of this project is that the system has succeeded in making it easier for admins to review, edit, and submit ticket data quickly and with minimal errors. The suggestion for the future is to develop a backend for data storage.